Impact of post‐haemorrhoidectomy pain relief checklists on pain outcomes: a randomized controlled trial. Issue 4 (16th February 2020) - Huang, Johnny; Rickard, Matthew J. F. X.; Keshava, Anil; Suen, Michael K. L.
Abstract: Background: Haemorrhoidectomy is associated with significant post‐operative pain which is primarily managed pharmacologically. Whether a non‐pharmacological adjunct such as a checklist can improve pain outcomes after an open haemorrhoidectomy has yet to be studied. The purpose of this study was to determine if a patient‐completed checklist of prescribed post‐haemorrhoidectomy pain medications would improve pain management after surgery. Methods: We conducted a dual‐centre randomized controlled trial of patients undergoing a Milligan‐Morgan haemorrhoidectomy for symptomatic third or fourth degree haemorrhoids. Thirty‐five patients were randomized into either a control group which received post‐operative pain medication plus a visual analogue scale (VAS) form, or an intervention group which received a post‐operative medication checklist in addition to the items the control group received. Both groups recorded their pain levels on the VAS forms at 10.00, 14.00 and 20.00 hours each day for 14 days post‐operatively. Results: Patients in the checklist group reported a significantly greater reduction in mean VAS pain score of 2.51 (95% confidence interval (CI) 1.34–3.68; P < 0.001) between day 1 post‐op and day 14 post‐op compared to 1.86 (95% CI 0.77–2.95; P = 0.001) for the control group. There was no significant difference between mean pain experienced by patients in either group over each of the 14 days individually or overall ( P = 0.07). Conclusion: The pain medication checklist lead to a greater reduction in pain between day 1 and 14 after an open haemorrhoidectomy compared to standard care but did not significantly reduce mean pain across any individual days or overall. Abstract : We conducted a dual‐centre randomized controlled trial to determine if a patient‐completed checklist of prescribed post‐operative pain medications would improve pain management after undergoing a Milligan‐Morgan haemorrhoidectomy for symptomatic third or fourth degree haemorrhoids. The pain medication checklist lead to a greater reduction in pain between day 1 to 14 after an open haemorrhoidectomy compared to standard care but did not significantly reduce mean pain across any individual days or overall.